Metabolism is not a Major Contributor to the Toxicity of Piperaquine, a Long-acting Antimalarial Agent in Artemisinin-based Combination Therapy - Zhang, Liyuan; Liu, Zhaohua; Zhang, Yunrui; Xie, Yuewu; Xing, Jie (Current Drug Metabolism, 2021)
Background: Hepatocellular damage has been reported for the antimalarial piperaquine (PQ) in the clinic after cumulative doses. Objectives: The role of metabolism in PQ toxicity was evaluated, and the mechanism mediating PQ hepatotoxicity was investigated. Methods: The toxicity of PQ and its major metabolite (PQ N-oxide; M1) in mice was evaluated in terms of serum biochemical parameters. The role of metabolism in PQ toxicity was investigated in mice pretreated with an inhibitor of CYP450 (ABT) and/or FMO enzyme (MMI). The dose-dependent pharmacokinetics of PQ and M1 were studied in mice. Histopathological examination was performed to reveal the mechanism mediating PQ hepatotoxicity. Results: Serum biochemical levels (ALT and BUN) increased significantly (P < 0.05) in mice after three-day oral doses of PQ (> 200 mg/kg/day), indicating hepatotoxicity and nephrotoxicity of PQ at a high dose. Weaker toxicity was observed for M1. Pretreatment with ABT and/or MMI did not increase PQ toxicity. PQ and M1 showed linear pharmacokinetics in mice after a single oral dose, and multiple oral doses led to their cumulative exposures. Histopathological examination showed that a high dose of PQ (> 200 mg/kg/day for three days) could induce hepatocyte apoptosis. The mRNA levels of targets in NF-ΚB and p53 pathways could be up-regulated by 2-30-fold in mice by PQ or M1. Conclusion: PQ metabolism led to detoxification of PQ, but there was a low possibility of altered toxicity induced by metabolism inhibition. The hepatotoxicity of PQ and its N-oxidation metabolite was partly mediated by NF-ΚB inflammatory pathway and p53 apoptosis pathway.
Keywords: metabolite